Health Factors in Islamic Perspectives and its Relation to Sustainability with Case Study at Traditional and Modern Mosque - Das, R; Qureshi, TS; Chowdhury, MSJ; Alam, MJB (Journal of Environmental Science and Natural Resources, 2012)
The study elucidates how health consideration integrated to the traditional, conventional and modern mosque design in Bangladesh. A literature survey is conducted to understandard the definition of health based on Islamic perspective. The purpose is to compare its sustainability and relationship with traditional and present design pattern of mosque. The literature study identifies four primary factors on health in the mosque design associated with natural lighting, ventilator, location of toilets and rainwater discharge. Analysis comprises design on natural lighting related to sun shading and indirect lighting, rainwater discharge related to rainwater deflection and leakages and wall openings related to natural cross air ventilation. In this study, Kalitikor Central Mosque, Bandar based on traditional pattern, Noyashorok Jamia Mosque and Amborkhana Jamia Mosque were chosen as modern type mosque. The analysis however shows the weakness that Kalitikor Central Mosque and Amborkhana Jamia Mosque design does not apply enough windows in the construction for opening furthermore Amborkhana Jamia Mosque design includes toilet facilities within the mosque. Noyashorok Jamia Mosque have sufficient opening in Back and left side however Amborkhana and Nayashork both of the mosque have no open windows facilities in its right hand side. The traditional toilet system is also a threat to health and safety factor. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11547 J. Environ. Sci. & Natural Resources, 5(1): 01-08, 2012